The Challenges and Strategies Used by EFL Teachers in Teaching Reading Comprehension - Andi Triandini Ramadhani Irving; Syarifuddin Dollah; Munir Munir (State University of Makassar, 2025)
This research aims to explore the challenges faced by English as a Foreign Language (EFL) teachers and the strategies they implement in teaching reading comprehension at MAS As’adiyah Puteri Pusat Sengkang. The research is grounded in the context of a semi-urban religious-based school where students generally have low exposure to English outside the classroom, limited vocabulary mastery, and low reading motivation. This research employed a descriptive qualitative approach, with data collected through classroom observation, in-depth interviews, and document analysis. The research involved two English teachers as key participants who regularly teach reading comprehension. The findings indicate four major challenges: (1) diverse student abilities, (2) lack of vocabulary mastery, (3) low student motivation and reading interest, and (4) time constraints. To address these issues, the teachers applied various strategies including (1) cognitive strategies (skimming, scanning, summarizing), (2) reciprocal teaching, (3) pre-reading strategies (activating prior knowledge), (4) independent reading, and (5) multimodal reading strategy. In conclusion, despite the multiple challenges in teaching reading comprehension in EFL classrooms, the application of appropriate, adaptive, and context-sensitive strategies can significantly enhance students’ reading ability and engagement in the learning process.Keywords: challenges, strategies, EFL teachers, reading comprehension